2021
DOI: 10.1021/acssensors.0c02330
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle-Based Potentiometric Sensing System for Continuous Monitoring of Multiple Electrolytes in Skin Interstitial Fluids

Abstract: Electrolytes play a pivotal role in regulating cardiovascular functions, hydration, and muscle activation. The current standards for monitoring electrolytes involve periodic sampling of blood and measurements using laboratory techniques, which are often uncomfortable/inconvenient to the subjects and add considerable expense to the management of their underlying disease conditions. The wide range of electrolytes in skin interstitial fluids (ISFs) and their correlations with those in plasma create exciting oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 61 publications
(107 reference statements)
0
41
0
Order By: Relevance
“…The concentration of these target biomarkers in ISF is consistent with those in the blood. [78] Li et al [79] designed an MNs sensing system that could monitor the electrolytes in the ISF. The biosensing system could selectively analyze Na + and K + in ISF and had the advantages of short detection time, high accuracy and repeatability.…”
Section: Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of these target biomarkers in ISF is consistent with those in the blood. [78] Li et al [79] designed an MNs sensing system that could monitor the electrolytes in the ISF. The biosensing system could selectively analyze Na + and K + in ISF and had the advantages of short detection time, high accuracy and repeatability.…”
Section: Electrolytementioning
confidence: 99%
“…a) The picture on the left was a schematic diagram of the MN sensor inserted into the skin, and the picture on the right was a potential sensing system composed of Na + selective electrode, K + selective electrode and Ag/AgCl reference electrode; b) optical image and SEM image of microneedle-based potential sensing system; c) modified Na + selective electrode, K + selective electrode and reference electrode; d) the optics image of MNs potential sensing system acting on chicken skin. Reproduced with permission [79]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…Li et al (2021) demonstrated a stainless-steel hollow microneedle-based potentiometric sensing system for continuous monitoring of multiple electrolytes in skin interstitial fluids. 55 These authors demonstrated monitoring of potassium and sodium ions by testing on phantom gel and chicken skin. Fig.…”
Section: Devices and Technologiesmentioning
confidence: 99%
“…(iii) Schematic illustration of steps for the functionalization of electrodes. Reproduced with permission from Li et al (2021). Copyright 2021 American Chemical Society.…”
Section: Mns For Multibiosensingmentioning
confidence: 99%